Border Wall Aesthetics: Artworks in Border Spaces - Ganivet, Elisa (transcript, 2019)
30 years after the fall of the Berlin Wall, we live in a time of globalization and free trade. Nevertheless, 70 new border walls have been built in this period – put together, they would cover the total circumference of the Earth. While governments offer manifold justifications for building these separation barriers, they invariably attract the attention of artists. Is it merely the lure of transgression, however, that attracts them – or is there a deeper significance in the artistic encounter with border walls? And which artistic strategies do these artists employ to approach them?In order to address these questions, Élisa Ganivet revisits the history of border wall aesthetics and compares more recent border-related works by 100 artists, including Joseph Beuys (Berlin), Banksy (Israel-Palestine), and Frida Kahlo (Mexico-US). Through art and thus beyond art, we understand the flaws and shortcomings of supposedly well-oiled systems.With a preface by Élisabeth Vallet.